FACTORS INFLUENCING BRAND IMAGE TO SILVERQUEEN CHOCOLATE PURCHASE DECISIONS - Nuri Aslami; Haris Muda (Journal of Social Research, 2022)
Background: The chocolate industry is one of the industries whose opportunities are quite large with increasing competition. Various chocolate brands such as Silverqueen, Cadbury, Toblerone, and others are trying to compete in the chocolate market. Objective: To find out the factors that influence the decision in the purchase of Silverqueen chocolate on PT. Mas Permai City branch of Pekanbaru city. Methods: This research uses a quantitative approach with primary data sources from interview results and secondary data from company data. The data is then analyzed with quantitative descriptive analysis. Results: It is expected of the company to price Silverqueen brand chocolates more. Because looking at the lowest number of brand image indicators about the price of Silverqueen brand chocolate affordable for Silverqueen brand chocolate consumers, then the company should pay more attention to the market price of Silverqueen brand chocolate to be more in demand outlet owners in buying Silverqueen chocolate. Conclusion: It is expected for the company to pay attention to any kind of factors that influence the purchase decision